Developing Professionally as an English Teacher: An Autoethnographic Study of ICT Tool Use During and After the Pandemic in Nepal - Karki, Sujeet; Neupane, Bharat; Sapkota , Rajesh (International Journal of Language and Literary Studies, 2024)
The COVID-19 pandemic interrupted Nepal's education system, forcing educators to rethink their classroom practices and transition from their physical classrooms to online platforms and other modes of teaching and learning. In this autoethnographic exploration, I draw from my significant experiences and practices about growing from a common to a techno-friendly teacher during and after the pandemic. Teacher professional development plays a dominant role in creating positive impacts on the lives of every teacher, especially during the pandemic days and transition. Hence, I reflected on the role of ICT in my professional growth and how they have influenced my professional journey. Subscribing experiential and transition theory, I interpreted my narratives, insights, and flashbacks about past incidents and interpreted them. The study reveals how an English language teacher struggled with ICT tools and other digital resources in the early days of the pandemic and felt vulnerable. These struggles, difficulties, vulnerabilities, and challenges in using ICT, including the applications, tools, and resources, and my resilience to cope with adversities, learning to use these tools, and the awaiting opportunities made a significant change in my teaching journey. My narratives, interpretations, and discussions showed the prominent role of ICT in the professional development of teachers.